2019
DOI: 10.1007/s11356-019-06600-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmentalism in the EU-28 context: the impact of governance quality on environmental energy efficiency

Abstract: Environmental policies are a significant cornerstone of a developed economy, but the question that arises is whether such policies lead to a sustainable growth path. It is clear that the energy sector plays a pivotal role in environmental policies, and although the current literature has focused on examining the link between energy consumption and economic growth through an abundance of studies, it does not explicitly consider the role of institutional or governance quality variables in the process. Both globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…A better quality of regulatory can make a better group of standards related to energy in countries and can solve the barriers to carry out energy efficiency projects leading to a higher energy efficiency level. This finding is in line with Wang et al (2004), Kaller et al (2018), Alam et al (2019) and Apergis and Garcia (2019) who proved the positive impact of regulatory quality on energy efficiency. The issued green bond shows positive impact on energy efficiency index which highlights the significant role of green bonds on enhancement of financing energy efficiency projects in OECD countries.…”
Section: Empirical Estimation Resultssupporting
confidence: 85%
“…A better quality of regulatory can make a better group of standards related to energy in countries and can solve the barriers to carry out energy efficiency projects leading to a higher energy efficiency level. This finding is in line with Wang et al (2004), Kaller et al (2018), Alam et al (2019) and Apergis and Garcia (2019) who proved the positive impact of regulatory quality on energy efficiency. The issued green bond shows positive impact on energy efficiency index which highlights the significant role of green bonds on enhancement of financing energy efficiency projects in OECD countries.…”
Section: Empirical Estimation Resultssupporting
confidence: 85%
“…Also, when analyzing the literature, one should highlight the fact that in terms of the issue of corporate responsibility for environmental damage, today the subject of attention of the international community is the positive duty of states to provide effective mechanisms for holding business entities liable for such violations, as well as in cases where entities management do not introduce mechanisms for assessing the risks of their activities for the environment, public health, environmental well-being of a particular community, and so on [6,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, political economy variables have a notable impact on understanding the relationship between urbanization and environmental degradation, which, in turn, affects CO 2 emissions and greenhouse gases. Furthermore, Apergis and Garćıa [46] and Ozturk et al [47] point out that governance quality is an important driver of energy efficiency and, hence, of environmental policies. In addition, Cansino et al [48] found robust evidence that both a higher level of institutional quality and a higher level of technological progress in 19 Latin America Countries act as inhibitors of greenhouse gas emissions into the atmosphere.…”
Section: Literature Reviewmentioning
confidence: 99%